HAUNTED BY MEMORY, SUSTAINED BY RESILIENCE: A STUDY OF POSTMODERN PARANOIA IN PREETI SHONEY’S WAKE UP, LIFE IS CALLING - THIRUMOORTHI. K, R. SHOBIA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Postmodern paranoia offers a lens to study the fractured self and the rising anxieties of the contemporary world, where people often struggle between memory and the uncertainty of life experiences. The strength of this approach is to show how literature brings out the complex mix of fear, endurance, and struggle to survive in unstable realities, without trauma. Preeti Shenoy’s Wake Up, Life is Calling follows the life of Ankita Sharma (Protagonist), who is haunted by her past but at the same time, holds on to resilience in herself to lead a normal life. The paper connects the postmodern paranoia in Shenoy’s narrative techniques, showing how memories become both sources of fear and survival, and how resilience helps to turn vulnerability into new possibilities. The study uses a qualitative method of close reading to examine how paranoia appears in the text through narrative breaks, shifting viewpoints, and psychological intensity. Secondary sources are used to mark the novel within postmodern ideas and the cultural context of Indian fiction. The analysis shows that the anxieties and uncertainties experienced by the protagonist are not merely destructive but also help her to face the past and explore new possibilities. The novel reflects the fear present in contemporary society while highlighting the power of hope, resilience, and self-reconstruction.